MEMPELAJARI CITARASA CUKO PEMPEK BUBUK DENGAN PENAMBAHAN ASAM SITRAT - Farliansyah, Farliansyah; Suyatno, Suyatno; Alhanannasir, Alhanannasir (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2014)
This research aims to study the effect of the addition of citric acid powder to taste cuko pempek and get the best treatment . This research was conducted in the laboratory of the Faculty of Agriculture, University of Muhammadiyah Palembang in July 2013 to December 2013. This study used a randomized block design (RBD ) are arranged in non- factor factorial with the addition of citric acid treatment consisting of five levels of treatment and repeated four times. Parameters observed in this study is the chemical analysis includes analysis of citric acid and pH levels , for the physical test is soluble viscosity and velocity , while for organoleptic test includes flavor, color and aroma cuko pempek powder by using multiple comparison test. Lowest levels of citric acid present in the A1 treatment (addition of citric acid 3g) with an average value of 0.469% , the highest pH found in the A1 treatment (addition of citric acid 3g) with an average value of 5.70. The rate was highest viscosity at A5 treatment (addition of citric acid 15g) with an average value of 2,271 cPs and speed pempek vinegar powder dissolves. Velocity is highest late in the A1 treatment (addition of citric acid 3 g) with an average value of 6.29 seconds. Test multiple comparison test sensory adding citric acid to the taste, color and aroma cuko pempek powder , found that treatment A1 has the taste, color and aroma of different unreal with cuko pempek comparator (cuko pempek standard) with the lowest average value of 28.45, 37.9%, 32.76%, which is almost the same as cuko pempek comparator (cuko pempek standard). cuko pempek To obtain powder authors suggest you should use the A1 treatment is the treatment of the addition of 3g of citric acid in powder 1000g pempek cuko materials.